A conceptualisation of the relationship between virtual experience and cybernauts' satisfaction with virtual communities. (2015) - Bouattour, Dorra; Debos, Franck; Abdellatif, Tarek
In this research, we developed and tested an integrated model relating individuals' satisfaction with their experiential values in virtual communities. Using a realised factorial analysis and regression, we identified the factors that influence member satisfaction in virtual communities. Adopting Mathwick et al.'s (2001) concept of experiential value, we proposed a conceptualisation of a virtual experience that fits closely with the original nomological framework advocated by Holbrook and Hirschman (1982).